If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -7y + 6 = 3(y + -1x) + -4 Reorder the terms: 6 + 2x + -7y = 3(y + -1x) + -4 Reorder the terms: 6 + 2x + -7y = 3(-1x + y) + -4 6 + 2x + -7y = (-1x * 3 + y * 3) + -4 6 + 2x + -7y = (-3x + 3y) + -4 Reorder the terms: 6 + 2x + -7y = -4 + -3x + 3y Solving 6 + 2x + -7y = -4 + -3x + 3y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 6 + 2x + 3x + -7y = -4 + -3x + 3x + 3y Combine like terms: 2x + 3x = 5x 6 + 5x + -7y = -4 + -3x + 3x + 3y Combine like terms: -3x + 3x = 0 6 + 5x + -7y = -4 + 0 + 3y 6 + 5x + -7y = -4 + 3y Add '-6' to each side of the equation. 6 + 5x + -6 + -7y = -4 + -6 + 3y Reorder the terms: 6 + -6 + 5x + -7y = -4 + -6 + 3y Combine like terms: 6 + -6 = 0 0 + 5x + -7y = -4 + -6 + 3y 5x + -7y = -4 + -6 + 3y Combine like terms: -4 + -6 = -10 5x + -7y = -10 + 3y Add '7y' to each side of the equation. 5x + -7y + 7y = -10 + 3y + 7y Combine like terms: -7y + 7y = 0 5x + 0 = -10 + 3y + 7y 5x = -10 + 3y + 7y Combine like terms: 3y + 7y = 10y 5x = -10 + 10y Divide each side by '5'. x = -2 + 2y Simplifying x = -2 + 2y
| 2(x-4)=-5 | | 3(2-4)=6(-2) | | 5d+6n=t | | (0)-3y=6 | | -1x-4=4 | | d-(-3)=100 | | -43=7-8t | | 16(y^2-9)-9x^2=0 | | 3y+7=2y-5 | | 2r^2+4r=2r^2-r | | 5r-13s=76 | | 3(x+4)-2=4 | | 3x-69=3 | | 0-3(-1)=6 | | -7f+4f=6 | | -3(5x+3)+4(6x+1)=43 | | 7+6q=67 | | C^2+4d^2-d^2= | | 6x+3-2x=15 | | -3n+6+5n=7n-8n+9 | | 7y+11=8-5y | | 9x-25=38 | | 2.5+1.5N=F | | n/9-4=-3 | | -3+6+5n=7n-8n+9 | | (n+5)=-2 | | -3(x-5)=4 | | 40-4x=5(4x+3)-5(-8-3x) | | 9x+-3x=36 | | 7+6x=67 | | 6(2x-1)+3=6(2-x)-1 | | 5x-4=(2/3)5x+4 |